An evaluation of an aids educational programme in industry: an exploratory study - Van der Velde, Patricia (Department of Psychology, 2024)
This study evaluates a small group educational programme on AIDS using a Solomon - Four group design. The research was conducted in 16 randomly selected Western Cape stores of a national supermarket chain. These stores were stratified into northern, central, southern· suburbs and outlying districts. Each group of 4 stores was assigned at random to either the treatment or control group of each component of the solomon - four according to their suburb stratification. 16 randomly selected weekly paid employees (8 males and a females) at each store were interviewed, by social work students, using an adapted version of the Temoshok (1987) questionnaire assessing knowledge and personal opinions about AIDS. Subjects were interviewed either pre and post education or post education only depending on which store (and hence which treatment group ) they were working in. A model to examine the probability of any subject knowing the "correct" answer to each item of the questionnaire was used in an item analysis of 16 knowledge questions and 22 personal opinion items using a BMDP logistic regression programme for binary data. Odds ratios and exact p values are reported for each item to determine the strengths and weaknesses of the educational programme and to pinpoint areas in the programme which need revision. Results indicated a significant improvement in knowledge in terms of the myths surrounding casual transmission of (HIV) AIDS and an improvement in knowledge on certain factual items. A statistically significant negative effect of education was evident in the section of the programme dealing with blood transfusions and contamination. Results also suggest a shift towards more desirable responses, on the personal opinion items of the questionnaire, towards people with AIDS particularly in those items which linked up with the educational programme. 67 subjects from the original sample who had received education were re-interviewed 2 months after the programme using all the knowledge questions and selected personal opinion items to determine what respondents had remembered or forgotten. These results suggest that the gains in knowledge were maintained on items dealing with casual transmission, and that the shifts towards more desirable responses on certain items were also maintained over the 2 month period. Recommendations for adjustments to the content of the programme are outlined.